Case Report: Ultrasound-guided interventional diagnosis and treatment of gastrosplenic fistula caused by lymphoma - Zhang, Yahan; Li, Yang; Li, Manxi; Song, Yu (Frontiers in Oncology, 2025)
Gastrosplenic fistula is a rare complication, most often secondary to gastric or splenic lymphoma. Severe gastrosplenic fistula can cause life-threatening upper gastrointestinal bleeding, making early diagnosis and intervention critical for a favorable prognosis. Currently, surgical intervention remains the primary treatment; however, outcomes are often suboptimal. In this paper, we present a case involving ultrasound-guided interventional diagnosis and treatment of gastrosplenic fistula caused by diffuse large B-cell lymphoma. An 18-year-old male initially presented with gastric distension and epigastric pain and was diagnosed with gastric non-Hodgkin lymphoma (diffuse large B-cell lymphoma) at an outside hospital before being referred to our institution for further management. Contrast-enhanced CT revealed an abnormal density lesion between the gastric fundus and spleen, suggestive of gastric perforation accompanied by adjacent exudation and localized abscess formation. A multidisciplinary team evaluation identified markedly elevated inflammatory markers and poor overall condition, rendering the patient unsuitable for immediate surgery. Subsequent B-mode ultrasound and contrast-enhanced ultrasound (CEUS) precisely delineated the fistula location and extent of the abscess, enabling determination of a safe puncture path. Ultrasound-guided percutaneous catheter drainage of the gastrosplenic fistula was then successfully performed. Post-procedural intracavitary contrast injection confirmed correct catheter tip placement distal to the fistula. Follow-up CT imaging 20 days after drainage showed a significant reduction in the encapsulated fluid and gas collection at the fistula site. After one month of clinical improvement, the patient underwent total gastrectomy with resection of the pancreatic body-tail and spleen. He was subsequently discharged and continued maintenance chemotherapy for non-Hodgkin lymphoma. At 13 months postoperatively, the patient remains clinically stable with normal vital signs.